MEMAHAMI HEGEMONI MEDIA MASSA BARAT DAN STRATEGI PEMBERITAAN TERHADAP DUNIA ISLAM - Nurdin, Nurdin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Western mass media is considered unfair and subjective in delivering news.  Instead previous studies show that those western mass media have unfairly broadcasted news related Muslim people, limited studies have been carried out to show how those media broadcast the news and who control those media. This study, therefore, tries to understand how western media broadcast news related Muslim people and who control those media. This study employed content analysis in which the data was gathered from online sources and scholar journals. The findings show that western media use some strategies in broadcasting news such as making early claims during broadcasting, present false report and negative image, and use unproper language. The conclusion is that unfair news broadcasting related Muslim countries could be happened due to Jews domination in western mass media ownership and management.  The limitation of this studi is that the data was merely gathered from online sources. Future research need to be carried out within broader context by involving journalists and communities.